Legal protection of women’s and children's rights after divorce through the E-MOSI CAPER App - Suadi, Amran; Candra, Mardi; Al Hasan, Fahadil Amin; Gumilar, Gugun (Jurnal Hukum Novelty, 2024)
Introduction to the Problem: Women and children are frequently mistreated, particularly when they face legal issues. In divorce situations, for example, they often do not receive the entitlements to which they are entitled, such as mut'ah, iddah, and child support. This situation is due to the existing legal system and policies that do not reflect equality and justice for women and children, particularly in the execution of court orders carrying ex-husbands' obligations to their ex-wives. One of the legal advances in this part is using information and technology (IT) to develop a decision execution system. E-MOSI CAPER is one of the IT-based decision execution instruments that ex-wives can employ to demand that their ex-husbands voluntarily carry out the decision's obligations.Purpose/Objective of the Study: This article attempts to describe and analyze how the E-MOSI CAPER App could assure the preservation of women's and children's rights after divorce.Design/Methodology/Approach: This work adopts a qualitative research technique through normative and empirical juridical approaches, with statutory and conceptual approaches.Findings: According to this study, the E-MOSI CAPER application, one of the IT-based services released by the Bengkulu Religious High Court, is an innovation that could be used as a tool in organizing guarantees for the protection of women's and children's rights. This App can increase the compliance of ex-husbands to perform court decisions, which makes this App part of the legal instrument of the Integrated Execution System.Paper Type: Research Article